Device and method for preparing graphene with controllable oxidation degree
By using a cyclic electrolysis method of porous inert metal electrodes and electrolytic reaction tubes in graphene preparation, the controllability and environmental protection problems are solved, and efficient and uniform graphene preparation is achieved.
Patent Information
- Application Number
- CN202411720063.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to achieve controllability of oxidation during the graphene preparation process, and traditional methods have problems of environmental protection and low production efficiency.
Porous inert metal is used as electrodes, and graphite raw materials are mixed with the electrolyte through an electrolytic reaction tube, and the material is circulated inside the sealing equipment by using the pressure to control the reaction pressure, voltage and reaction time to achieve controllability of oxidation.
It realizes the relative controllability of graphene oxidation, improves the preparation efficiency, has good product uniformity and consistency, is suitable for industrial production, and the process is relatively green and environmentally friendly.
Smart Images

Figure CN119530845A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene oxide preparation equipment and process, and in particular to a device and method for preparing graphene with controllable oxidation degree. Background Art
[0002] As a two-dimensional carbon material with only one atomic layer thickness, graphene has a series of advantages such as excellent flexibility and electrical conductivity, and is therefore widely used in many fields. The redox method is the most commonly used and most promising method for preparing graphene. However, during the oxidation process, the generation of a large number of oxygen-containing functional groups destroys the conjugated structure of graphene. Therefore, it is necessary to remove the oxygen-containing functional groups to obtain reduced graphene oxide to repair the structure and restore its high conductivity. When graphene is used in many fields, it is required to have high conductivity and a certain amount of oxygen-containing functional groups or defects. Therefore, it is particularly necessary to control the degree of oxidation of graphene, not only to make full use of the advantages of oxygen-containing functional groups and ensure the conductivity of graphene, but also to obtain reduced graphene oxide with controllable functional group types and contents according to the application requirements of graphene, so as to realize the diversified application of graphene materials.
[0003] In the invention patent application with publication number CN104386677A, entitled A micro-oxidized graphene and its preparation method, it is disclosed that the micro-oxidized graphene obtained by using graphene with a relatively complete lattice structure as a raw material and introducing an appropriate amount of oxygen-containing functional groups on its surface has good dispersibility, chemical reactivity and excellent physical properties. However, it is necessary to introduce strong alkali and strong oxidants to treat the graphene, and the reaction is not environmentally friendly.
[0004] The invention patent application with publication number CN116328745A and titled "A hydrophilic and hydrophobic controllable sulfide porous graphene material and preparation method thereof" discloses that vegetable oil, elemental sulfur and nano- and submicron-sized fused quartz powders are mixed and heated for sulfidation, and then carbonized at high temperature to obtain a sulfide graphene material wrapped with fused quartz particles, and porous sulfide graphene is obtained by hot alkali dissolution. The porous graphene is mixed with graphene oxide to obtain a product. However, the reaction involves materials such as sulfur powder / vegetable oil, which have an impact on subsequent graphene processing and is not environmentally friendly.
[0005] The invention patent application with publication number CN116873914A, entitled A graphene with controllable surface structure and its preparation method, discloses that graphite, acid and oxidant are mixed and reacted, the obtained graphite intercalation compound is reacted with perborate, and then the reaction product is centrifuged and washed to neutrality and then dispersed in water for exfoliation to obtain graphene. This reaction also involves a large amount of strong acid such as concentrated sulfuric acid, which is not conducive to environmental protection and post-processing.
[0006] The above methods cannot take into account the advantages of being green, convenient, and easy to mass produce. Moreover, after testing, the controllable oxidation degree of these methods is not optimistic. It is difficult to obtain products with stable and consistent oxidation degree with the same raw materials and reaction conditions. Therefore, a device and method for preparing graphene with controllable oxidation degree is urgently needed to solve this problem. Summary of the invention
[0007] The object of the present invention is to provide a device and method for preparing graphene with controllable oxidation degree, so as to solve the problems mentioned in the above background technology.
[0008] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a device for preparing graphene with controllable oxidation degree, comprising an electrolytic reaction tube, a storage barrel and a feed pump, wherein one end of the electrolytic reaction tube is connected to the outlet end of the feed pump through a feed valve, and the other end is connected to the storage barrel through a discharge valve, and the discharge end of the storage barrel is connected to the inlet end of the feed pump; a liquid replenishment port is provided at the upper end of the storage barrel; an anode porous filter element is installed in the electrolytic reaction tube, which is an inert porous electrode in the shape of a hollow tube, used for adhering graphite raw materials and passing electrolyte; a cathode rod is penetrated inside the anode porous filter element, the two do not contact, and one end of each of them passes through the electrolytic reaction tube for electrical connection to a power source.
[0009] Preferably, the electrolytic reaction tube is vertically arranged, with a feed port at the lower end and a discharge port at one side of the upper part, and the two are respectively connected to the feed valve and the discharge valve through flanges; a sleeve is fixedly arranged inside the electrolytic reaction tube, the anode porous filter is arranged in the sleeve, and there is no gap between the two ends of the anode porous filter and the sleeve, the sleeve is fixedly connected to the inner wall of the electrolytic reaction tube and a drainage collection space is left, and the two ends of the sleeve are sealed to the inner wall of the electrolytic reaction tube; a liquid outlet connected to the drainage collection space is opened on one side of the middle part of the outer wall of the electrolytic reaction tube and is connected to a liquid outlet valve for drainage, and a plurality of through holes are opened on the sleeve within the range of the drainage collection space for discharging the electrolyte that passes through the anode porous filter during drainage.
[0010] Preferably, one end of the anode porous filter element is connected to a plurality of rod-shaped conductive connecting rods, the connecting rods are arranged parallel to the cathode rods, and the connecting rods are connected to the anode pole ears after passing through the electrolysis reaction tube.
[0011] Preferably, the material of the anode porous filter element is porous titanium foam with a pore size of 0.1 to 100 μm. When it is necessary to improve the adhesion of the graphite raw material and the permeability of the electrolyte, the pore size of the anode porous filter element is selected to be 20 to 50 μm; the electrolytic reaction tube is made of surface-insulated pressure-resistant materials, including plastics or metal materials with surface insulation coating treatment.
[0012] Preferably, a pipeline liquid pressure gauge resistant to acid and alkali corrosion is provided at the feed end of the electrolytic reaction tube to detect the working pressure of the electrolyte in the pipeline.
[0013] Another technical solution provided by the present invention is a method for preparing graphene with controllable oxidation degree, which adopts the above-mentioned device and includes the following specific steps: uniformly mixing the graphite raw material and the electrolyte and pouring them into a storage barrel, turning on the feed pump to start circulation, adjusting the appropriate reaction pressure in the electrolytic reaction tube through the valve opening and the feed pump during the circulation process, turning on the power supply, energizing the anode porous filter element and the cathode rod, controlling the appropriate reaction voltage, starting the reaction, and obtaining the graphene sample after reaching the required reaction time.
[0014] Preferably, the reaction pressure is between 0.2 and 0.8 MPa; the reaction voltage is between 3 and 50 V, and the reaction time is between 4 and 10 hours.
[0015] Preferably, the above method also includes: after reaching the required reaction time, first opening the liquid outlet to discharge the electrolyte that has passed through the anode porous filter element, and after most of the electrolyte is discharged, closing the feed pump and taking out the reacted graphene concentrate from the storage barrel.
[0016] Preferably, the graphite raw material is selected from expanded graphite, flake graphite, graphite powder, and worm graphite, with a mesh size of 10 to 400 meshes, and the electrolyte is one or a combination of sulfuric acid, sodium sulfate, ammonium sulfate, potassium sulfate, ammonium bisulfate, sodium bisulfate, potassium bisulfate, persulfate, phosphate, oxalic acid, citric acid, and nitric acid. The corresponding system cationic base is used as an adjustment. For the production of low-oxidation products, an electrolyte with a pH close to neutral is selected, and for the production of high-oxidation products, an electrolyte with an acidic pH is selected; after the graphite raw material and the electrolyte are mixed, the solid content is controlled at 0.5 to 10wt%, and the overall room temperature viscosity of the mixed raw material is controlled at 100 to 2000mpas. When it is necessary to increase the reaction efficiency while increasing the circulation rate to reduce the clogging of the anode porous filter element, the overall room temperature viscosity of the mixed raw material is controlled at 500 to 1000mpas; during the reaction, materials are added to the storage barrel and / or the reaction pressure is changed to adapt to the continuous increase in viscosity in the system as the graphene raw material is peeled off.
[0017] Preferably, the above method produces graphene products with consistent oxygen content using the same raw materials, the same equipment and the same reaction conditions.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The device and method for preparing graphene with controllable oxidation degree adopts porous inert metal as electrode and flaky, granular or powdered graphite raw material as initial material. With the help of pressure, the electrolyte material mixed with graphite raw material is circulated inside the closed device. During the circulation process, the graphite raw material adheres to the energized porous electrode, which can ensure that the graphite raw material is always in contact with the electrode, thereby ensuring continuous electrolysis and improving the efficiency of exfoliation preparation of graphene. By controlling the circulation reaction parameters, a graphene product with a relatively controllable oxidation degree can be prepared.
[0020] 2. The device and method for preparing graphene with controllable oxidation degree are easy to use and operate, and can use flake graphite or graphite powder that does not have self-supporting properties as raw materials. Compared with graphite paper, the preparation efficiency is greatly improved. The preparation process is relatively green and environmentally friendly. The prepared products have good uniformity and consistency and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the three-dimensional structure of the preparation device of the present invention;
[0022] Figure 2 It is a schematic diagram of the main structure of the preparation device of the present invention;
[0023] Figure 3 It is a schematic diagram of the main structure of the electrolytic reaction tube of the present invention;
[0024] Figure 4 For along Figure 3 Schematic diagram of the cross-sectional structure in the AA direction;
[0025] Figure 5 It is a left-side structural schematic diagram of the electrolytic reaction tube of the present invention;
[0026] Figure 6 For along Figure 5 Schematic diagram of the cross-sectional structure in the middle BB direction;
[0027] Figure 7 For along Figure 3 Schematic diagram of the cross-sectional structure in the CC direction;
[0028] In the above picture:
[0029] 1. Electrolysis reaction tube; 2. Storage barrel; 3. Feed pump; 4. Feed valve; 5. Liquid discharge valve; 6. Discharge valve; 7. Liquid filling port;
[0030] 1-1, anode ear; 1-2, cathode rod; 1-3, anode porous filter element; 1-4, feed inlet; 1-5, liquid outlet; 1-6, discharge outlet.
[0031] Figure 8The first sampling physical comparison is for Example 1 (left side of the figure) and Example 6 (right side of the figure);
[0032] Figure 9 The oxygen content test results of the graphene samples prepared twice in parallel in Example 1;
[0033] Figure 10 The oxygen content test results of the graphene samples prepared twice in parallel in Example 2;
[0034] Figure 11 The oxygen content test results of the graphene samples prepared twice in parallel in Example 3;
[0035] Figure 12 The oxygen content test results of the graphene samples prepared twice in parallel in Example 4;
[0036] Figure 13 The oxygen content test results of the graphene samples prepared twice in parallel in Example 5;
[0037] Figure 14 The oxygen content test results of the graphene samples prepared twice in parallel in Example 6;
[0038] Figure 15 The oxygen content test results of the graphene samples prepared twice in parallel in Comparative Example 1;
[0039] Figures 9 to 15 The left pictures are for the first parallel test, and the right pictures are for the second parallel test. DETAILED DESCRIPTION
[0040] See also Figures 1 to 7 , a device for preparing graphene with controllable oxidation degree, comprising an electrolytic reaction tube 1, a storage barrel 2 and a feed pump 3, wherein one end of the electrolytic reaction tube 1 is connected to the outlet end of the feed pump 3 through a feed valve 4, and the other end is connected to the storage barrel 2 through a discharge valve 6, and the discharge end of the storage barrel 2 is connected to the inlet end of the feed pump 3; a liquid replenishment port 7 is opened at the upper end of the storage barrel 2; an anode porous filter element 1-3 is installed in the electrolytic reaction tube 1, which is an inert porous electrode in the shape of a hollow tube, used for attaching graphite raw materials and passing electrolyte; a cathode rod 1-2 is penetrated inside the anode porous filter element 1-3, the two do not contact, and one end of each passes through the electrolytic reaction tube 1 for electrical connection to a power source.
[0041] In a preferred embodiment, the electrolytic reaction tube 1 is arranged vertically, with a feed port 1-4 at the lower end and a discharge port 1-6 at one side of the upper part, and the two are respectively connected to the feed valve 4 and the discharge valve 6 through flanges;
[0042] In order to more conveniently obtain the concentrated product after the reaction is completed, the following specific structure can be adopted, see Figure 4 ,6 7: A sleeve is fixedly provided inside the electrolytic reaction tube 1, and the anode porous filter 1-3 is arranged in the sleeve, and there is no gap between the two ends of the anode porous filter 1-3 and the sleeve, the sleeve is fixedly connected to the inner wall of the electrolytic reaction tube 1 and a drainage collection space is reserved, and the two ends of the sleeve are sealed and connected to the inner wall of the electrolytic reaction tube 1. The connection between the sleeve and the electrolytic reaction tube 1 can be connected by multiple connecting rods as shown in the figure, or other methods can be adopted, such as fixed connection at only two ends, as long as the drainage collection space is reserved; a liquid outlet 1-5 connected to the drainage collection space is opened on one side of the middle part of the outer wall of the electrolytic reaction tube 1 A liquid outlet valve 5 is connected for draining liquid, and a plurality of through holes are provided on the sleeve within the range of the drainage collection space, which are used for discharging the electrolyte that passes through the anode porous filter element 1-3 during drainage. Due to the slow permeation rate, the number of through holes can increase the processing time after the reaction is completed; in addition, in order to facilitate the emptying of the drainage collection space during maintenance, a cleaning hole can also be opened on one side of the bottom; this drainage structure is not necessary for production, but it is beneficial to improve efficiency. If there is no such structure, the product in the storage barrel 2 can be taken out and then concentrated after the reaction is completed; in order to facilitate the removal of the product, the storage barrel 2 should preferably adopt a container with an openable upper cover.
[0043] like Figure 4 and 5 As shown, one end of the anode porous filter element 1-3 can be connected to a plurality of rod-shaped conductive connecting rods, which are arranged parallel to the cathode rod 1-2. After the connecting rods pass through the electrolysis reaction tube 1, they are connected to the anode pole ear 1-1. Under the above-mentioned preferred vertical arrangement scheme of the electrolysis reaction tube 1, the connecting rods are more suitable for passing through the electrolysis reaction tube 1 from above.
[0044] For reference, the material of the anode porous filter element 1-3 can be porous titanium foam, and the pore size can generally be controlled in the range of 0.1 to 100 μm according to different products. When it is necessary to improve the adhesion of the graphite raw material and the permeability of the electrolyte, the pore size of the anode porous filter element 1-3 can be further selected to be 20 to 50 μm. If the pore size is too small, a filter cake layer is easily formed quickly on the anode surface and pore blockage is easy to occur, which is not conducive to the uniformity of the overall reaction of the material. If the pore size is too large, the overall reaction surface area of the anode decreases and the reaction efficiency decreases. The electrolytic reaction tube 1 should preferably use a surface-insulated pressure-resistant material, including plastics (such as PB, PE, PVC, PERT, PPR, etc.) or metal materials with surface insulation coating (such as coated polytetrafluoroethylene stainless steel, etc.).
[0045] In addition, for pressure monitoring, a pipeline liquid pressure gauge resistant to acid and alkali corrosion may be provided at the feed end of the electrolytic reaction tube 1 to detect the working pressure of the electrolyte in the pipeline.
[0046] After using the above device, the graphene product can be prepared by referring to the following steps:
[0047] The graphite raw material and the electrolyte are uniformly mixed and poured into the storage barrel 2. The liquid level can be controlled at about 2 / 3 of the storage barrel 2;
[0048] Turn on the feed pump 3 to start the circulation. During the circulation, adjust the appropriate reaction pressure in the electrolytic reaction tube 1 through the valve opening and the feed pump 3. Turn on the power supply, energize the anode porous filter element 1-3 and the cathode rod 1-2, control the appropriate reaction voltage, and start the reaction.
[0049] After the desired reaction time is reached, the graphene sample is obtained.
[0050] The reaction pressure should be further controlled between 0.2 and 0.8 MPa. The specific control method can be achieved by adjusting the opening of the feed valve 4 and the discharge valve 6 (the two valves can use manual valves or solenoid control valves to achieve more precise control); reaction pressure control is very important. The pressure directly affects the circulation flow rate of the system. If the pressure is too low, the material and the anode hole will not fit tightly. If the pressure is too high, the electrolyte will flow too fast and the feed pump will heat up too fast, resulting in the system temperature out of control, which is not conducive to oxidation degree control; the following will be further explained in conjunction with the comparative example.
[0051] In addition, under normal circumstances, the reaction voltage can be controlled to be 3 to 50 V, and the reaction time can be controlled to be 4 to 10 hours.
[0052] In the case of having the drainage collection space in the above preferred scheme, the above method may also include the following steps: after reaching the required reaction time, first open the liquid outlet 1-5 to discharge the electrolyte that has passed through the anode porous filter element 1-3, and after most of the electrolyte is discharged, close the feed pump 3 and take out the reacted graphene concentrate from the storage barrel 2.
[0053] Among the above raw materials, the graphite raw material can be selected from expanded graphite, flake graphite, graphite powder, worm graphite, etc., with a mesh size of 10 to 400 meshes, and the electrolyte is one or a combination of sulfuric acid, sodium sulfate, ammonium sulfate, potassium sulfate, ammonium hydrogen sulfate, sodium hydrogen sulfate, potassium hydrogen sulfate, persulfate, phosphate, oxalic acid, citric acid, nitric acid, etc., and is adjusted by a corresponding system cationic base such as ammonia water, sodium hydroxide, potassium hydroxide, etc.; in addition, for the production of low-oxidation products, an electrolyte with a pH close to neutral, such as sulfate, is preferred, and for the production of high-oxidation products, an electrolyte with an acidic pH, such as oxidizing persulfate, phosphate, nitrate, etc. is preferred;
[0054] After the graphite raw material is mixed with the electrolyte, the solid content is controlled at 0.5-10wt%, and the overall room temperature viscosity of the mixed raw material is controlled at 100-2000mpas. When it is necessary to improve the reaction efficiency and the circulation rate to reduce the clogging of the anode porous filter 1-3, the overall room temperature viscosity of the mixed raw material is controlled at 500-1000mpas. During the reaction, the material is added to the storage barrel 2 and / or the reaction pressure is changed to adapt to the continuous increase in viscosity in the system as the graphene raw material is peeled off. In addition, under the premise of ensuring the normal operation of the reaction, it is advisable to increase the viscosity of the system as much as possible to improve the reaction efficiency. However, if the viscosity is too high, it is easy to cause the feed pump 3 to be overloaded, the system circulation rate to decrease, and the porous electrode to be blocked. In addition, as the graphene raw material is peeled off, the viscosity in the system will continue to increase, so the pressure in the system is adjusted to adapt to the liquid transportation problem caused by the viscosity change, which cannot be ignored.
[0055] The method of the present invention can produce graphene products with consistent oxygen content under the same raw materials, the same equipment and the same reaction conditions.
[0056] The above invention is further explained below in combination with several embodiments and comparative examples, but it should be noted that these are only a few embodiments of the present invention and should not be used as an absolute limitation of the present invention; the parallel tests in the following embodiments refer to the same equipment, the same conditions, the same raw materials, and are prepared in batches at different times.
[0057] Embodiment 1:
[0058] A porous anode with an average pore size of 20um and 200-mesh expanded graphite were selected as raw materials. Ammonium sulfate with a concentration of 0.1M and potassium bisulfate with a concentration of 0.05M were used as the main electrolyte. The pH value was adjusted to 7.5 with ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 5% was prepared. The initial viscosity of the system was measured to be 533mpas. The mixed liquid was poured into a storage barrel, and then the feed pump was turned on to start the circulation. During the circulation process, the reaction pressure was adjusted to 0.2Mpa, and the power was turned on at the same time. The voltage was controlled to 5V and the reaction was continued for 4h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the two samples were 4.49 and 6.93at.% respectively.
[0059] For detailed test results, see Figure 9 And the following Table 1 and Table 2:
[0060] Table 1: First sampling test results of Example 1
[0061] Name Start BE Peak BE End BE Heiaht CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 283.93 279.18 239926.59 0.83 320020.77 4540.17 95.51 O1s 544.98 531.71 525.18 8496.62 3.83 38345.7 213.23 4.49
[0062] Table 2: Second sampling test results of Example 1
[0063] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 283.8l 279.18 144030.66 1.02 233077.16 3306.5 93.07 O1s 544.98 532.24 525.18 10937 3.35 44270.01 246.26 6.93
[0064] Embodiment 2:
[0065] A porous anode with an average pore size of 0.1um and 10-mesh high-purity graphite powder were selected as raw materials. Ammonium sulfate with a concentration of 0.5M and sodium bisulfate with a concentration of 0.1M were used as the main electrolyte. The pH value was adjusted to 6.5 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 10% was prepared. The initial viscosity of the system was measured to be 2200mpas. The mixed solution was poured into a storage barrel, and then the feed pump was turned on to start the cycle. During the cycle, the reaction pressure was adjusted to 0.2Mpa, and the power supply was turned on at the same time. The control voltage was 8V and the reaction lasted for 4h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the samples obtained twice were 14.33 and 14.06at.% respectively.
[0066] For detailed test results, see Figure 10 and Tables 3 and 4 below.
[0067] Table 3: First sampling test results of Example 2
[0068] Name Start BE Peak BE End BE Heiaht CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 283.57 279.18 130532.22 1.06 237818.28 3373.36 85.67 O1s 544.98 531.54 525.18 25732.74 3.39 101452.69 564.1 14.33
[0069] Table 4: Second sampling test results of Example 2
[0070] Name Start BE Peak BE Endd BE Height CPS FWHM eV Area(P)CPS.eV Area(N)TPP-2M Atomic% C1s 297.98 283.73 279.18 252320.5 1.01 449365.36 6296.86 85.46 O1s 544.98 531.78 525.18 68632.75 2.19 178599.99 1036 14.06
[0071] Embodiment three:
[0072] A porous anode with an average pore size of 10um and 400-mesh worm graphite were selected as raw materials. Sodium sulfate with a concentration of 1M and sodium bisulfate with a concentration of 0.1M were used as the main electrolyte. The pH value was adjusted to 6.5 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 8% was prepared. The initial viscosity of the system was measured to be 430mpas. The mixed liquid was poured into a storage barrel, and then the feed pump was turned on to start the cycle. During the cycle, the reaction pressure was adjusted to 0.3Mpa, and the power supply was turned on at the same time. The control voltage was 8V and the reaction lasted for 5h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the two samples were 17.76 and 19.17at.% respectively.
[0073] For detailed test results, seeFigure 11 And the following Tables 5 and 6:
[0074] Table 5: First sampling test results of Example 3
[0075] Name Start BE Peak BE End BE Heiaht CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 284.08 279.18 94905.97 1.36 234094.56 3321.38 82.24 O1s 544.98 532.14 525.18 28990.83 3.95 128933.77 717.17 17.76
[0076] Table 6: Second sampling test results of Example 3
[0077] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N)TPP-2M Atomic% C1s 297.98 283.79 279.18 178796.78 1.2 381236.42 5342.41 80.25 O1s 544.98 531.85 525.18 90921.72 2.06 220014.9 1276.3 19.17
[0078] Embodiment 4:
[0079] A porous anode with an average pore size of 30um and 250-mesh flake graphite were selected as raw materials. Sodium persulfate with a concentration of 0.5M and ammonium bisulfate with a concentration of 0.03M were used as the main electrolyte. The pH value was adjusted to 6.5 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 8% was prepared. The initial viscosity of the system was measured to be 540mpas. The mixed liquid was poured into a storage barrel, and then the feed pump was turned on to start the cycle. During the cycle, the reaction pressure was adjusted to 0.4Mpa, and the power supply was turned on at the same time. The control voltage was 15V and the reaction lasted for 6h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the samples obtained twice were 20.27 and 22.68at.%, respectively.
[0080] For detailed test results, see Figure 12 And the following Tables 7 and 8:
[0081] Table 7: First sampling test results of Example 4
[0082] Name Start BE Peak BE End BE Heiaht CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 284.52 279.18 93140.96 1.32 213983.2 3036.7 79.73 O1s 544.98 532.4 525.18 58348.01 2 138781.19 772.07 20.27
[0083] Table 8: Second sampling test results of Example 4
[0084] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N)TPP-2M Atomic% C1s 297.98 283.98 279.18 158234.14 1.36 380411.92 5331.47 76.72 01s 544.98 531.88 525.18 113249.19 2.07 271634.22 1575.78 22.68
[0085] Embodiment five:
[0086] A porous anode with an average pore size of 50um and 200-mesh flake graphite were selected as raw materials. Ammonium persulfate with a concentration of 0.8M and oxalic acid with a concentration of 0.6M were used as the main electrolyte. The pH value was adjusted to 6 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 1.5% was prepared. The initial viscosity of the system was measured to be 102mpas. The mixed solution was poured into a storage barrel, and then the feed pump was turned on to start the cycle. During the cycle, the reaction pressure was adjusted to 0.6Mpa, and the power supply was turned on at the same time. The control voltage was 40V and the reaction lasted for 8h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the samples obtained twice were 24.07 and 25.14at.%, respectively.
[0087] For detailed test results, see Figure 13 And the following Tables 9 and 10:
[0088] Table 9: First sampling test results of Example 5
[0089] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 284.6 279.18 85032.52 1.41 206676.05 2933.12 75.93 O1s 544.98 532.36 525.18 64972.81 2.24 167106.09 929.62 24.07
[0090] Table 10: Second sampling test results of Example 5
[0091] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N)TPP-2M Atomic% C1s 297.98 283.97 279.18 151690.84 1.39 369275.76 5175.38 74.27 01s 544.98 531.76 525.18 120463.38 2.21 301996.94 1751.75 25.14
[0092] Embodiment six:
[0093] A porous anode with an average pore size of 100um and 400-mesh expanded graphite were selected as raw materials. Ammonium persulfate with a concentration of 1M and 0.1M nitric acid were used as the main electrolyte. The pH value was adjusted to 5.5 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 9% was prepared. The initial viscosity of the system was measured to be 1800mpas. The mixed solution was poured into a storage barrel, and then the feed pump was turned on to start the cycle. During the cycle, the reaction pressure was adjusted to 0.8Mpa, and the power supply was turned on at the same time. The control voltage was 50V and the reaction lasted for 8h. The liquid outlet was then opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the samples obtained twice were 30.11 and 28.91at.%, respectively.
[0094] For detailed test results, see Figure 14 And the following Tables 11 and 12:
[0095] Table 11: First sampling test results of Example 6
[0096] Name Start BE Peak BE End BE Height CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 286.27 279.18 75237.46 1.48 253018.24 3593.81 69.89 O1s 544.98 532.03 525.18 128852.55 1.87 278367.49 1548.26 30.11
[0097] Table 12: Second sampling test results of Example 6
[0098] Name Start BE Peak BE End BE Heiaht CPS FWHM eV Area(P)CPS.eV Area(N) Atomic% C1s 297.98 284.28 279.18 52448.33 1.67 163402.36 2318.61 71.09 O1s 544.98 531.75 525.18 77022.89 1.94 169524.43 942.72 28.91
[0099] Comparative Example 1:
[0100] The reaction pressure is set to 0.1 MPa, and the other parameters refer to Example 2, specifically:
[0101] A porous anode with an average pore size of 0.1um and 10-mesh high-purity graphite powder were selected as raw materials. Ammonium sulfate with a concentration of 0.5M and sodium bisulfate with a concentration of 0.1M were used as the main electrolyte. The pH value was adjusted to 6.5 by ammonia water. After sufficient stirring, a mixed reaction liquid with a solid content of 10% was prepared. The initial viscosity of the system was measured to be 2200mpas. The mixed liquid was poured into the storage barrel, and then the feed pump was turned on to start the cycle. During the circulation process, the reaction pressure was adjusted to 0.1Mpa, and the power was turned on at the same time. The control voltage was 8V and the reaction lasted for 4h. Then the liquid outlet was opened to discharge the electrolyte. After most of the electrolyte was discharged from the liquid outlet, the power supply of the circulation pump was turned off. The reacted graphene concentrate was taken out from the storage barrel to obtain a graphene sample. After two parallel tests, the oxygen content test results of the two samples were 23.84% and 15.05% respectively.
[0102] For detailed test results, see Figure 15 And the following Tables 13 and 14:
[0103] Table 13: Comparative Example 1 First Sampling Test Results
[0104] Name Peak BE Height CPS FWHM eV Area(P)CPS.eV Atomic% C1s 284.8 51790.11 1.42 129350.61 75.24 O1s 532.61 52115.73 1.85 108437.4 23.84
[0105] Table 14: Second sampling test results of comparative example 1
[0106] Name Start BE Peak BE End BE Heiqht CPS FWHM eV Area(P)CPS.eV Area(N)TPP-2M Atomic% C1s 297.98 284.47 279.18 200156.52 1.03 326342.83 4575.15 84.95 O1s 544.98 532.19 525.18 52073.78 2.37 139702.25 810.63 15.05
[0107] The overall results of the embodiments and comparative examples are summarized in Table 15 below:
[0108] Table 15: Comparison of reaction conditions and results of examples and comparative examples
[0109]
[0110] From the above examples and comparative test results, it can be seen that the parallel test products in comparative example 1 have poor consistency, indicating that it is difficult to ensure the controllability of the oxidation degree under 0.1Mpa. The reason for this may be that the reaction pressure is low, resulting in the graphite raw material being unable to adhere well to the anode wall; on the other hand, due to the medium and high viscosity solution, a certain pressure is required for driving. If the pressure is too low, the liquid mass transfer is uneven, which will cause the core electrolysis area to be locally oxidized all the time, and other parts will hardly react, which will eventually lead to a great difference in the oxidation degree of the product. The situation shown is that the products obtained under the same conditions have a large difference in oxidation degree; and in the embodiment, the six groups of products obtained by the parallel test have a significantly smaller difference in oxidation degree. Therefore, the reaction pressure control in this method is very important.
[0111] In addition, the present invention also carried out parallel tests within each embodiment, and the products prepared in a single time had good uniformity in various places, and no uneven quality of products in the same batch was found.
[0112] The cyclic electrolysis scheme for preparing graphene by electrochemical method provided by the present invention adopts porous inert metal as electrode and flaky, granular or powdered graphite raw material as initial material. With the help of pressure, the material is circulated inside a closed device. The present invention continues to carry out relevant experiments. Under the condition of the same batch of materials, as the reaction time changes, the oxidation degree of the graphene product changes accordingly, and the process is relatively controllable. The reason may be that, compared with the existing method that requires the use of graphite rods or graphite paper for continuous preparation, the continuous circulation of the graphite raw material of the present invention can ensure that the reaction raw materials on the electrode are more similar, and the farthest end of the smallest unit material adsorbed on the electrode is closer to the electrode, which is more in line with the characteristics of the reaction process advancing over time without interference from other conditions.
[0113] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0114] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A device for preparing graphene with controllable oxidation degree, characterized in that: The invention comprises an electrolytic reaction tube (1), a material storage barrel (2) and a feed pump (3), wherein one end of the electrolytic reaction tube (1) is connected to the outlet end of the feed pump (3) through a feed valve (4), and the other end is connected to the material storage barrel (2) through a discharge valve (6), and the discharge end of the material storage barrel (2) is connected to the inlet end of the feed pump (3); a liquid replenishing port (7) is provided at the upper end of the material storage barrel (2); an anode porous filter element (1-3) is installed in the electrolytic reaction tube (1), which is a hollow tubular inert porous electrode used for attaching graphite raw materials and passing electrolyte; a cathode rod (1-2) is inserted into the interior of the anode porous filter element (1-3), the two do not contact each other, and one end of each of the cathode rods passes through the electrolytic reaction tube (1) for electrical connection to a power source.
2. The device for preparing graphene with controllable oxidation degree according to claim 1, characterized in that: The electrolytic reaction tube (1) is arranged vertically, with a feed port (1-4) provided at the lower end and a discharge port (1-6) provided at one side of the upper part, and the two are respectively connected to the feed valve (4) and the discharge valve (6) through flanges; a sleeve is fixedly provided inside the electrolytic reaction tube (1), an anode porous filter element (1-3) is arranged in the sleeve, and there is no gap between the two ends of the anode porous filter element (1-3) and the sleeve, the sleeve is fixedly connected to the inner wall of the electrolytic reaction tube (1) and a drainage collection space is reserved, and the two ends of the sleeve are sealedly connected to the inner wall of the electrolytic reaction tube (1); a liquid outlet (1-5) connected to the drainage collection space is provided on one side of the middle part of the outer wall of the electrolytic reaction tube (1) and is connected to a liquid outlet valve (5) for drainage, and a plurality of through holes are provided on the sleeve within the range of the drainage collection space, which are used to discharge the electrolyte that has passed through the anode porous filter element (1-3) during drainage.
3. The device for preparing graphene with controllable oxidation degree according to claim 1, characterized in that: One end of the anode porous filter element (1-3) is connected to a plurality of rod-shaped conductive connecting rods, the connecting rods are arranged parallel to the cathode rods (1-2), and the connecting rods are connected to the anode pole ears (1-1) after passing through the electrolysis reaction tube (1).
4. The device for preparing graphene with controllable oxidation degree according to claim 1, characterized in that: The material of the anode porous filter element (1-3) is porous titanium foam with a pore size of 0.1 to 100 μm. When it is necessary to improve the adhesion of the graphite raw material and the permeability of the electrolyte, the pore size of the anode porous filter element (1-3) is selected to be 20 to 50 μm. The electrolytic reaction tube (1) is made of a surface-insulated pressure-resistant material, including plastic or a metal material with a surface insulation coating.
5. The device for preparing graphene with controllable oxidation degree according to claim 1, characterized in that: The feed end of the electrolytic reaction tube (1) is provided with a pipeline liquid pressure gauge resistant to acid and alkali corrosion, which is used to detect the working pressure of the electrolyte in the pipeline.
6. A method for preparing graphene with controllable oxidation degree, using the device according to any one of claims 1 to 5, characterized in that: The method comprises the following specific steps: uniformly mixing graphite raw material and electrolyte and pouring the mixture into a storage barrel (2), turning on a feeding pump (3) to start circulation, adjusting a suitable reaction pressure in an electrolytic reaction tube (1) by means of a valve opening and the feeding pump (3) during the circulation, turning on a power source, energizing an anode porous filter element (1-3) and a cathode rod (1-2), controlling a suitable reaction voltage, starting a reaction, and obtaining a graphene sample after a required reaction time has been reached.
7. A method for preparing graphene with controllable oxidation degree according to claim 6, characterized in that: The reaction pressure is between 0.2 and 0.8 MPa; the reaction voltage is between 3 and 50 V; and the reaction time is between 4 and 10 hours.
8. A method for preparing graphene with controllable oxidation degree according to claim 6, characterized in that: The electrolytic reaction tube (1) is fixedly provided with a sleeve inside, the anode porous filter element (1-3) is arranged in the sleeve, and there is no gap between the two ends of the anode porous filter element (1-3) and the sleeve, the sleeve is fixedly connected to the inner wall of the electrolytic reaction tube (1) and a drainage collection space is reserved, and the two ends of the sleeve are sealedly connected to the inner wall of the electrolytic reaction tube (1); a liquid outlet (1-5) connected to the drainage collection space is provided on one side of the middle part of the outer wall of the electrolytic reaction tube (1) and is connected to a liquid outlet valve (5), and a plurality of through holes are provided on the sleeve within the range of the drainage collection space; The method further comprises: after the required reaction time is reached, first opening the liquid outlet (1-5) to discharge the electrolyte that has passed through the anode porous filter element (1-3); after most of the electrolyte has been discharged, closing the feed pump (3) to take out the reacted graphene concentrate from the storage barrel (2).
9. A method for preparing graphene with controllable oxidation degree according to claim 6, characterized in that: The graphite raw material is selected from expanded graphite, flake graphite, graphite powder, and worm graphite, and the mesh number is 10 to 400 meshes. The electrolyte is one or a combination of sulfuric acid, sodium sulfate, ammonium sulfate, potassium sulfate, ammonium hydrogen sulfate, sodium hydrogen sulfate, potassium hydrogen sulfate, persulfate, phosphate, oxalic acid, citric acid, and nitric acid. The corresponding system cationic base is used as an adjustment. For the production of low-oxidation products, an electrolyte with a pH close to neutral is selected, and for the production of high-oxidation products, an electrolyte with an acidic pH is selected; After the graphite raw material and the electrolyte are mixed, the solid content is controlled at 0.5-10wt%, and the overall room temperature viscosity of the mixed raw material is controlled at 100-2000mpas. When it is necessary to improve the reaction efficiency and the circulation rate to reduce the clogging of the anode porous filter (1-3), the overall room temperature viscosity of the mixed raw material is controlled at 500-1000mpas. During the reaction, materials are added to the storage barrel (2) and / or the reaction pressure is changed to adapt to the continuous increase in viscosity in the system as the graphene raw material is peeled off.
10. The method for preparing graphene with controllable oxidation degree according to claim 7, characterized in that: The method can produce graphene products with consistent oxygen content under the same raw materials, the same equipment and the same reaction conditions.
Citation Information
Patent Citations
Micro-oxidized graphene and preparation method thereof
CN104386677A
Hydrophilicity and hydrophobicity controllable vulcanized porous graphene material and preparation method thereof
CN116328745A
Graphene with controllable surface structure and preparation method thereof
CN116873914A